2020
DOI: 10.3390/jrfm13090204
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Foreign Direct Investment and Trade on Labor Productivity Growth in Vietnam

Abstract: Among developing Asian countries that have accelerated their integration with the global economy, Vietnam has achieved remarkable economic development. Vietnam’s development strategy prioritizing the promotion of trade and foreign direct investment (FDI) resulted in the rapid transformation of its industrial structure from an agro-based one to one led by the export-oriented manufacturing sector in the past three decades. Given the importance of labor productivity growth on the structural transformation, the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
1
9
1
1
Order By: Relevance
“…The result of this study found that foreign investment has an insignificant positive effect on labor productivity in 33 provinces of Indonesia. The positive sign of the coefficient is in 10.12928/optimum.v12i2.5227 line with Derado and Darko (2019) and Asada (2020), who explained that foreign investment provides breakthroughs to increasing labor productivity. According to the findings of Boghean and State (2015), foreign investment has a significant positive relationship with labor productivity in 20 European countries.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…The result of this study found that foreign investment has an insignificant positive effect on labor productivity in 33 provinces of Indonesia. The positive sign of the coefficient is in 10.12928/optimum.v12i2.5227 line with Derado and Darko (2019) and Asada (2020), who explained that foreign investment provides breakthroughs to increasing labor productivity. According to the findings of Boghean and State (2015), foreign investment has a significant positive relationship with labor productivity in 20 European countries.…”
Section: Resultssupporting
confidence: 66%
“…Foreign investment (FDI) is also useful in providing breakthroughs in labor productivity (Derado and Darko, 2019). In line with Asada (2020), FDI contributes to increasing labor productivity through technology transfer, the introduction of production processes, and better management skills. Moreover, multinational companies usually have access to the latest and most advanced technology that is expected to enter and spread to local companies to increase the productivity of the host country.…”
Section: Introductionmentioning
confidence: 99%
“…These results agree with Casale and Posel's (2005) results from South Africa, with those of Fatima and Sultana (2009) from Pakistan, and with those of Akyuz and Dogan (2017) from Turkey. Our results are also not far from those of Asada (2020), who focused on foreign direct investments through the ARDL method and concluded that Vietnam developed its strategy to enhance the positive and constructive relationship between FDI, trade, and labor productivity. Asada (2020, p. 2) mentions that "The driving forces of the structural transformation include capital accumulation and technology transfer through FDI as well as the reallocation of labor from sectors with lower labor productivity to sectors with higher labor productivity, notably export-oriented manufacturing sector.…”
contrasting
confidence: 53%
“…They are estimated at USD 1.5 billion due to mining, industry, energy, etc. Asada (2020) emphasized that FDI plays a remarkable role in the socio-economic development of countries, especially developing ones, and he pointed out that if most Asian countries have successfully integrated into the world economy, it is partly due to FDI.…”
mentioning
confidence: 99%
“…The foreign direct investment is the driving force of structural transformation for host countries (Zaman and Vasile 2012;Beatrice 2013;Kottaridi and Filippaios 2015;Islam et al 2018;Asada 2020;Ioan et al 2020;Djokoto 2021). The beneficial effects of foreign capital are felt on several levels, but differently depending on the characteristics and potential of the host country (Iacovoiu and Panait 2014;Voica and Mirela 2014;Ullah et al 2015;Erkomaishvili et al 2018;Islam et al 2020;Gupta et al 2021;Kyove et al 2021).…”
Section: Introductionmentioning
confidence: 99%